A fluoride-selective electrode (Fse) for the quantification of fluoride in lithium-ion battery (Lib) electrolytes. Issue 38 (6th September 2016) - Wilken, A.; Kraft, V.; Girod, S.; Winter, M.; Nowak, S.
Abstract : In this work, a fluoride-selective electrode (FSE) was applied with regard to the analysis of fluoride in lithium hexafluorophosphate-based lithium-ion battery (LIB) electrolytes. Abstract : In this work, a fluoride-selective electrode (FSE) was applied with regard to the analysis of fluoride in lithium hexafluorophosphate-based lithium-ion battery (LIB) electrolytes. The influence of linear organic carbonate solvents dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) which are used as co-solvents in battery electrolytes was investigated. The developed FSE method for the analysis of battery electrolytes was comprehensively validated in view of the (1) trueness and recovery rates (nominal vs. actual comparison; influence of different amounts of electrolytes on the performance of the electrode; recovery rates of defined differences in concentration), (2) precision (intra-day precision and inter-day precision), (3) selectivity (influence of the carbonate solvents on different fluoride concentrations; interferents) and (4) linearity and range. Statistical analysis was performed to evaluate the data and to characterize the reproducibility of the method. The determination of the commercially available LP30 (1 mol LiPF6 and ethylene carbonate/dimethyl carbonate (EC : DMC, 50 : 50 wt%)) electrolyte stored over 47 days and at 80 °C, by the FSE technique was compared to the fluoride analysis by ion chromatography (IC). While interferences in the IC method resulted in false-high concentrations, the FSE operated free from interferences, selective and specific. The validation of the method was successfully carried out and enables new areas of application.